McNicol-2019-NPCTR-SOC-map - McNicol, Gavin; Bulmer, Chuck; D'Amore, David D.; Sanborn, Paul; Saunders, Sari; Giesbrecht, Ian; Gonzalez Arriola, Santiago; Bidlack, Allison; Butman, David; Buma, Brian (Dryad Digital Repository, 2018)
This raster [.tif] is the predicted soil organic carbon for the North Pacific coastal temperate rainforest. Content is displayed in megagrams of carbon per hectare (Mg ha-1) to 1 m in mineral soil, plus overlying organic horizons. Map values are the output of a random forest machine learning algorithm trained on pedon data from within British Columbia and southeast Alaska only, therefore confidence is low for predictions south of the US-Canada border and predictions in that region have not been validated. Lakes, glaciers and ice-fields have also not been masked from the map. More information on the map can be found in the associated manuscript.